Prostanoid receptors (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Prostanoid receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on Prostanoid Receptors [644]) are activated by the endogenous ligands prostaglandins PGD2, PGE1, PGE2 , PGF2α, PGH2, prostacyclin [PGI2] and thromboxane A2. Measurement of the potency of PGI2 and thromboxane A2 is hampered by their instability in physiological salt solution; they are often replaced by cicaprost and U46619, respectively, in receptor characterization studies.